2020
DOI: 10.1101/2020.03.09.972307
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Force-dependent recruitment of Piezo1 drives adhesion maturation and calcium entry in normal but not tumor cells

Abstract: Piezo1 is a mechanosensitive Ca 2+ -permeable channel that has been implicated in a number of mechanosensing processes. It is diffusive on plasma membranes and activated by local membrane tension changes yet recent data suggest that Piezo1 activity is tightly coupled to the integrin-mediated actin cytoskeleton through a poorly understood mechanism. In our studies, we found that Piezo1 stably localizes to RGD matrix adhesions in normal but not in transformed cells. Piezo1 binding requires contractility and trig… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 92 publications
(199 reference statements)
4
24
0
Order By: Relevance
“…4). A recent study has shown that Piezo1 is recruited to FAs in normal cells but not in transformed cells including HEK (Yao et al, 2020), that observation was done on a uniform substrate, consistent with our control cells.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…4). A recent study has shown that Piezo1 is recruited to FAs in normal cells but not in transformed cells including HEK (Yao et al, 2020), that observation was done on a uniform substrate, consistent with our control cells.…”
Section: Discussionsupporting
confidence: 92%
“…4c). Piezo1 can be recruited to FAs(Yao et al, 2020), our results show that co-localization of Piezo1 and FAs does not occur when the cells are in the relaxed state.…”
Section: Resultsmentioning
confidence: 79%
“…Their main advantage for our study is that they can be easily transfected with large constructs like Piezo1 (2521 amino acids, Uniprot entry Q92508) while endogenous Piezo1 expression level is low. Publications connecting Piezo1 to mechano-signaling mediated by integrins are based mainly on Piezo1-mediated elevation of intracellular Ca 2+ , entering the cytosol either from the extracellular space [ 57 ] or from the endoplasmic reticulum [ 29 ]. As PiCS is not suppressed in our hands by blocking Piezo1 ion channel activity using antibiotics, including streptomycin, it is unlikely that Ca 2+ influx via the plasma membrane is required for PiCS and matrix stiffness sensing.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reported the association of Piezo1 with peripheral mature adhesion. 23,24 Hence, we examined if ultrasound treatment promoted Piezo1 translocation to the peripheral adhesions located in the plasma membrane of tumor cells. Cells transiently transfected with mApple-paxillin were used to determine the adhesion distribution.…”
Section: Piezo1 Channel Mediated-calcium Influx Is Required For Tumormentioning
confidence: 99%